Jubileusz 90-lecia urodzin profesora Władysława Kupiszewskiego - Lewaszkiewicz, Tadeusz (Slavia Occidentalis, 2024)
The object of this article are the academic and organisational achievements of W. Kupiszewski, a professor of the University of Warsaw. The professor researched mainly Polish dialectology and the history of the Polish language. The article contains covers of Prof. Kupiszewski’s books.